Results of the patient report of intermittent catheterization experience (PRICE) study. Issue 8 (13th September 2021) - Roberson, Daniel; Newman, Diane K.; Ziemba, Justin B.; Wein, Alan; Stambakio, Hanna; Hamilton, Rita G.; Callender, Librada; Holderbaum, Leah; King, Tamara; Jackson, Angela; Tran, Thanh; Lin, George; et al.
Abstract: Aims: Patient satisfaction is paramount to health‐related quality of life (HR‐QoL) outcomes. High quality, quantitative data from the US describing patients' actual experiences, difficulties, and HR‐QoL while on an intermittent self‐catheterization (ISC) regimen is very scarce. Our objective was to better understand patient practices with and attitudes towards ISC. Methods: This is a cross‐sectional, multi‐centered, clinical study of adult men and women performing ISC in the United States. Data collected included demographics, medical history, catheter characteristics, specific self‐catheterization habits and two validated HR‐QoL questionnaires: The Intermittent Self‐Catheterization Questionnaire (ISC‐Q) and the Intermittent Catheterization Difficulty Questionnaire (ICDQ). Results: Two hundred participants were recruited from six sites; 70.0% were male, 73.5% were Caucasian with a median age was 51.0 years (range 19–90 years). The ISC‐Q showed that the vast majority of participants reported ease with ISC (82.0% satisfaction score) had confidence in their ability to perform ISC (91.9% satisfaction score); yet, many felt self‐conscious about doing so (58.3% satisfaction score) and had concerns about long‐term adverse effects (58.1% satisfaction score). The ICDQ indicated little to no difficulty for most participants with all routine ISC practices. A small minority of participants reported some difficulty with a "blocking sensation" during initiation of catheterization, leg spasticity, and painful catheterization. Multivariate linear regression results are also reported. Discussion/Conclusion: Participants are confident with ISC and have little overall difficulty, which may be a product of successful education and/or catheter design. urinary tract infections (UTIs) were common (yet variable) and may contribute to the noted long‐term ISC concerns. Limitations exist including various selection biases leading to concerns of external validity. Future educational interventions in this population may further improve HR‐QoL, optimize UTIs prevention, and diminish concerns with long‐term ISC.